Polypyrrole derivatives for detection of toxic gases: A theoretical study - Coleone, Alex Pifer [UNESP]; Barboza, Bruno Hori [UNESP]; Batagin-Neto, Augusto [UNESP] (Wiley, 2021)
Polypyrrole (PPy) based compounds have been considered interesting materials for several technological applications, mainly due to their unique optoelectronic properties and high versatility of synthesis. In particular, the sensitivity of their electrical properties to external stimuli defines these polymers as promising candidates for chemical sensor applications. However, the demanding processes involved in the synthesis of 3-4 substituted PPy derivatives hinders the development of optimized systems. In this report, electronic structure calculations were conducted for a set of branched PPy derivatives aiming to identify promising compounds for chemical sensors. The calculations were carried out in the framework of the density functional theory (DFT), by considering oligomeric systems. The influence of the side groups on the local reactivities and adsorption centers of the compounds were evaluated via condensed-to-atoms Fukui indexes and molecular electrostatic potentials. DFT-based adsorption studies and fully atomistic reactive molecular dynamics (FARMD) simulations were conducted for selected systems considering toxic gases as analytes. The results point out PPy, PPy-CCH and PPy-CN as promising candidates for chemical sensor applications, presenting high potential for the detection of Cl2 and SO2. FARMD results indicate that the analysis of local reactivities and electrostatic potentials can be used to identify relevant adsorption centers and possible degradation processes.
Keywords: chemical sensors; electronic structure calculations; polypyrrole derivatives; reactivity; toxic gases adsorption